Systematic review of Neotropical genera of Lauxaniidae: 3. The genus Paracestrotus Hendel, 1925 (Diptera: Schizophora) - Silva, Vera Cristina (Zootaxa, 2006)
A review of the Neotropical Lauxaniidae genus Paracestrotus Hendel, 1925 is presented with redescription of P. gibbosus Hendel, 1925 and the description of a new species, P. pulchripennis sp. n., from Brazil, Pará, including illustrations and a key.